Analysis of changes in lattice parameter of a grade 91 steel during thermal ageing at 550 °C. (March 2019) - Fetni, Seifallah; Jhinaoui, Walid; Boubahri, Chokri; Montero, David; Briki, Jalel
Abstract: Microstructural changes in the T91 steel (also known as the modified 9Cr1Mo steel), largely used in thermal and nuclear power plants as well as petrochemical factories, have been studied, after isothermal ageing (at 550 °C) in laboratory, for different durations up to 7000 h (about 10 months of exposure). In-depth analysis about chemical and structural changes in the metallic substrate and secondary carbides (M23 C6 ) were conducted using SEM, EDX and X-ray diffraction instrumentations. Results reveal a progressive restoration of the tempered martensitic matrix with holding time. Then, a continuous increase in size of secondary carbides was noticed until stabilization after >5000 h of ageing. Kinetic parameters of matrix lattice were determined using Johnson-Mehl-Avrami (JMA) model. Natural logarithm of the relative lattice parameter of the matrix varies linearly with that of ageing time. Thus, the Avrami exponent n and activation energy E were established. Diffusion of chromium and molybdenum from matrix into carbides lattice was proved which explains their continuous coarsening. That has a harmful effect on the long term stability of the microstructure. The time-temperature dependence of this transformation could be then a good indicator to assess the resistance of T91 steel to heat exposure.